ChemInform Abstract: A Practical and Stereoselective Organocatalytic Alkylation of Aldehydes with Benzodithiolylium Tetrafluoroborate. Issue 39 (September 2015) - Gualandi, Andrea; Mengozzi, Luca; Giacoboni, Jessica; Saulnier, Steve; Ciardi, Moira; Cozzi, Pier Giorgio
Abstract Review: 56 refs.